PENERAPAN RME UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DI KELAS VI MIN 11 TABALONG - MASHURI MASHURI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2023)
Realistic Mathematics Education (RME) is a learning model by connecting to something real in everyday life. This study aims to increase student activity and learning outcomes, as well as teacher learning process activities in class VI MI Negeri 11 Tabalong in learning mathematics on Building Space material through the RME approach. This research is a classroom action research conducted in two cycles. Each cycle consists of two meetings which go through four stages of implementation, namely planning, implementing action, observing, and reflecting. The type of data used is in the form of quantitative and qualitative data. Data collection techniques using tests and non-tests. The results showed that in the first cycle the average value of student learning outcomes was 68.31 with classical learning mastery of 53.33%, students' activeness in the learning process was 71.98% with high criteria, and the value of teacher learning process activities was 80.64 (B+ ). In cycle II, the average value of student learning outcomes was 84.33 with 100% classical learning completeness, student activity in the learning process was 79.20% with very high criteria, and the value of teacher learning process activities was 89.14 (A+). These results show an increase from cycle I to cycle II. Based on the results obtained, it can be concluded that the RME approach is proven to be able to increase student learning activities and outcomes, as well as teacher activities in the learning process. ABSTRAKRealistic Mathematics Education (RME) merupakan suatu model pembelajaran dengan menghubungkan pada sesuatu yang nyata dalam kehidupan sehari-hari. Penelitian ini bertujuan untuk meningkatkan aktivitas dan hasil belajar siswa, serta kegiatan proses pembelajaran guru di kelas VI MI Negeri 11 Tabalong pada pembelajaran matematika materi Bangun Ruang melalui pendekatan RME. Penelitian ini merupakan penelitian tindakan kelas yang dilaksanakan dalam dua siklus. Setiap siklus terdiri dari dua pertemuan yang melalui empat tahap pelaksanaan yaitu perencanaan, pelaksanaan tindakan, pengamatan, dan refleksi. Jenis data yang digunakan berupa data kuantitatif dan kualitatif. Teknik pengumpulan data menggunakan tes dan non tes. Hasil penelitian menunjukkan bahwa pada siklus I rata-rata nilai hasil belajar siswa 68,31 dengan ketuntasan belajar klasikal 53,33%, keaktifan siswa dalam proses pembelajaran 71,98% dengan kriteria tinggi, dan nilai kegiatan proses pembelajaran guru 80,64 (B+). Pada siklus II, rata-rata nilai hasil belajar siswa 84,33 dengan ketuntasan belajar klasikal 100%, keaktifan siswa dalam proses pembelajaran 79,20% dengan kriteria sangat tinggi, dan nilai kegiatan proses pembelajaran guru 89,14 (A+). Hasil tersebut menunjukkan peningkatan dari siklus I ke siklus II. Berdasarkan hasil yang diperoleh, dapat disimpulkan bahwa pendekatan RME terbukti dapat meningkatkan aktivitas dan hasil belajar siswa, serta kegiatan guru dalam proses pembelajaran .